Glycoconjugates of Mucochloric Acid-Synthesis and Biological Activity - Katarzyna Żurawska; Daria Burdalska; Magdalena Skonieczna; Anna Byczek-Wyrostek; Anahit Dawicka; Anna Kasprzycka; Krzysztof Walczak (MDPI AG, 2023)
The pharmacological effects of the presence of a sugar moiety, 1,2,3-triazole ring and silyl groups in the structure of biologically active compounds have been extensively studied in drug design and medicinal chemistry. These components can be useful tools to tailoring the bioavailability of target molecules. Herein we present the study on the impact of the sugar substituent structure and triisopropylsilyl group presence on the anticancer activity of mucochloric acid (MCA) derivatives containing the furan-2(5H)-one or 2H-pyrrol-2-one core. The obtained results clearly indicated that tested compounds caused a significant decrease in cell viability of HCT116 and MCF-7 cell lines. MCF-7 cells indicate serious resistance toward investigated compounds in comparison with HCT116 cell line, it suggests that estrogen-dependent breast cancer cells are significantly less sensitive to the tested derivatives. Depending on the structure of the sugar, the type and site of connection with the furanone or 2H-pyrrol-2-one derivative and the presence of the silyl group, the selectivity of the compound towards cancer cells can be controlled. The obtained results may have an impact on the design of new furanone-based anticancer compounds.